A critical review of research on strategies in learning Chinese as both a second and foreign language - Jiang, Xiaoli; Cohen, Andrew D. (Studies in Second Language Learning and Teaching, 2012)
This article critically reviews strategy research on learning Chinese both as a second and foreign language. Through a careful examination of major data bases in both the Chinese and English languages, the article summarizes research in the field and the principal research methods used in the studies reviewed. Moreover, key limitations in research designs, inconsistencies in reported findings, inappropriate use of research methods, and weaknesses in both Chinese- and English-language publications are discussed. The article concludes by calling for future research paying more attention to current language learning strategy theories and practices.